2019
DOI: 10.1111/1365-2656.12945
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability affects the prevalence of a microsporidian parasite

Abstract: Defining the relationship between nutrients and parasitism is complicated by shifts in host physiology and population density, which can both mediate the effects of host diet on parasites and vice versa. We examined the relationship between nutrient availability and an abundant parasite capable of both horizontal and vertical transmission (Hamiltosporidium tvaerminnensis) of a planktonic crustacean, Daphnia magna, in rock pools on Baltic Sea Skerry islands. We found that the relative availability of nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Such medicinal properties have been suggested for the common cyanobacterium Microcystis aeruginosa against two parasites of Daphnia: the viral agent of white fat cell disease (Coopman, Muylaert, Lange, Reyserhove, & Decaestecker, 2014) and the yeast Metschnikowia bicuspidata (Sánchez, Huntley, Duffy, & Hunter, 2019). Overall, despite the substantial effort to relate the fitness of Daphnia parasites to single factors, such as food quality (Hall, Knight, et al, 2009a;Sánchez et al, 2019), nutrient availability (Frost, Ebert, & Smith, 2008;Narr, Ebert, Bastille-Rousseau, & Frost, 2019) and water temperature (Cuco, Castro, Gonçalves, Wolinska, & Abrantes, 2018;Vale et al, 2008), the combined effects of these stressors remain relatively unexplored in this system (but see Garbutt, Scholefield, Vale, & Little, 2014). As cyanobacteria blooms and heat waves are concurrent phenomena in nature (Joehnk et al, 2008), a comprehensive approach is required to make better epidemiological predictions in freshwater ecosystems.…”
mentioning
confidence: 99%
“…Such medicinal properties have been suggested for the common cyanobacterium Microcystis aeruginosa against two parasites of Daphnia: the viral agent of white fat cell disease (Coopman, Muylaert, Lange, Reyserhove, & Decaestecker, 2014) and the yeast Metschnikowia bicuspidata (Sánchez, Huntley, Duffy, & Hunter, 2019). Overall, despite the substantial effort to relate the fitness of Daphnia parasites to single factors, such as food quality (Hall, Knight, et al, 2009a;Sánchez et al, 2019), nutrient availability (Frost, Ebert, & Smith, 2008;Narr, Ebert, Bastille-Rousseau, & Frost, 2019) and water temperature (Cuco, Castro, Gonçalves, Wolinska, & Abrantes, 2018;Vale et al, 2008), the combined effects of these stressors remain relatively unexplored in this system (but see Garbutt, Scholefield, Vale, & Little, 2014). As cyanobacteria blooms and heat waves are concurrent phenomena in nature (Joehnk et al, 2008), a comprehensive approach is required to make better epidemiological predictions in freshwater ecosystems.…”
mentioning
confidence: 99%
“…While disease agents have been studied extensively, the COVID-19 pandemic and the rising awareness of climate change emphasize the need to better understand the factors affecting disease outbreaks. Various studies have shown that abiotic factors, predation on free-living stages, host size, age, behaviour and diet can all alter the infectivity, survival, richness and abundance of parasites [3][4][5][6][7][8]. Studies of the impact of environmental factors on parasites mainly focus on the indirect effects of this impact on the host immune system or intrinsic host-parasite interactions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on infection in cladocerans have primarily focused on their survival and offspring production in laboratory settings [ 22 , 23 , 24 ], and very few interactions, such as their defense strategies against infection, have been studied. Empirical studies have tried to associate infection with cladocerans by considering the effects of single factors [ 25 , 26 ], such as food quality [ 27 , 28 ], nutrient availability [ 29 ], and water temperature [ 30 ], on their survival and mortality. For example, elevated water temperatures increase the abundance of certain food resources, such as cyanobacteria, and reduce the food quality of cladocerans [ 31 ].…”
Section: Introductionmentioning
confidence: 99%